化简 (1)f(x)=(sinx-cosx)平方-1 (2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2化简(1)f(x)=(sinx-cosx)平方-1(2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 15:09:54
化简(1)f(x)=(sinx-cosx)平方-1(2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2化简(1)f(x)=(sinx-cosx)平方-1(2)f(x)=根号3s
化简 (1)f(x)=(sinx-cosx)平方-1 (2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2化简(1)f(x)=(sinx-cosx)平方-1(2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2
化简 (1)f(x)=(sinx-cosx)平方-1 (2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2
化简
(1)f(x)=(sinx-cosx)平方-1
(2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2
化简 (1)f(x)=(sinx-cosx)平方-1 (2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2化简(1)f(x)=(sinx-cosx)平方-1(2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2
(1)f(x)=(sinx-cosx)平方-1=(sinx)^2+(cosx)^2-2sinxcosx-1=-sin2x
(2)f(x)=根号3sinxcosx-cosxsin(π/2+x)-1/2=根号3sinxcosx-cosxsin(π/2-x)-1/2
=根号3/2*sin2x-(cosx)^2-1/2
=根号3/2*sin2x-(1+cos2x)/2-1/2
=根号3/2*sin2x-1/2*cos2x-1/2
=sin(2x-π/6)-1
f(sinx)=1+cos(2x),求f(x),
设f(sinx)=cos2x+1求f(cos*x)
f(sinx+1/sinx)=csc^2x-cos^2x 求f(x)
若 f(sinx+1/sinx)=csc^2x-cos^2x,求f(x)
求函数f(x)=cos^2x+sinx-1
f(cos)=-cos(2x),则f(sinx)
f(1+sinX)=2+cos^2X
f(x)=cos(sinx)求导
已知f(1+sinx)=2+sinx+cos^2,求f(x)的解析式
f(x)=(-1+sinx+cos^2 x)/(1-sinx)的奇偶性的证明
判断f(x)=(1+sinx-cos^2x)/(1+sinx)的奇偶性
已知函数f(x)=sinx(1+sinx)+cos平方x
函数f(x)=(2sinx+cos^2x)/(1+sinx)值域
f ' (sinx)=cos^2x,求f(x)
f(x)=(1/2)(sinx+cos)-(1/2)|sinx-cosx|的值域
f(x)=(1/2)(sinx+cos)-(1/2)|sinx-cosx|的值域
若f(sinx)=cos2x,那么f(cos x)=?
f(2sinx-1)=cos^2x,则f(x)=